Downy mildew effector HaRxL106 interacts with the transcription factor BIM1 altering plant growth, BR signaling and susceptibility to pathogens - Bogino, María Florencia (2024)
Hyaloperonospora arabidopsidis (Hpa) is an oomycete pathogen that causes downy mildew disease on Arabidopsis. This obligate biotroph manipulates the homeostasis of its host plant by secreting numerous effector proteins, among which are the RxLR-effectors. Identifying the host targets of effectors and understanding how their manipulation facilitates colonization of plants is key to improve plant resistance to pathogens. Here we characterize the interaction between the RxLR effector HaRxL106 and BIM1, an Arabidopsis transcription factor (TF) involved in Brassinosteroid (BR) signaling. We report that HaRxL106 interacts with BIM1 in vitro and in planta. BIM1 is required by the effector to increase the host plant susceptibility to (hemi)biotrophic pathogens, and thus can be regarded as a susceptibility factor. Mechanistically, HaRxL106 requires BIM1 to induce the transcriptional activation of BR-responsive genes and cause alterations in plant growth patterns that phenocopy the shade avoidance syndrome. Our results support previous observations of antagonistic interactions between activation of BR signaling and suppression of plant immune responses and reveal that BIM1, a new player in this crosstalk, is manipulated by the pathogenic effector HaRxL106.